Periodic Transition between Breathing Spots and Synchronous Sulfur Deposition/Dissolution in Transpassive Region of the Electro‐Oxidation of Sulfide on Platinum. Issue 8 (1st June 2017) - Pan, Changwei; Cheng, Ruolan; Birzu, Adrian; Yang, Jiaping; Ren, Lin; Varela, Hamilton; Gao, Qingyu
Abstract: In the transpassive region of sulfide electro‐oxidation on platinum, the system displayed different complex oscillations under potentiostatic control experiments, changing from quasiperiodic small oscillations to alternate modes between small and large amplitude oscillations for increasing applied voltages. In each period of the alternating‐mode oscillations, the current density evolves from a slightly decreasing steady state to small and large amplitude oscillations. Spatiotemporal patterns developed on the platinum disk were recorded with a CCD camera and ranged from breathing spots to alternating patterns between breathing spots and synchronous deposition/dissolution. Karhunen‐Loève decomposition analysis of the experimental patterns showed that the twinkling patterns had multiple modes each with a low percentage of energy, whereas the alternate patterns were mainly characterized by one dominant mode. Abstract : Ride the wave: Complex oscillations with a small amplitude group and a large amplitude peak in one period cause periodic transitions between twinkling spots and synchronous sulfur deposition/dissolution on a platinum disk in the transpassive region of the electro‐oxidation of sulfide.